Clinical and microbiological characteristics of paracoccidioidomycosis in patients with AIDS in Buenos Aires, Argentina. (15th March 2019) - Messina, F; Romero, M; Benchetrit, A; Marin, E; Arechavala, A; Depardo, R; Negroni, R; Santiso, G
Abstract: Paracoccidioidomycosis (Pm) is a systemic disease, endemic in the American continent. There are two different clinical forms, the infant-juvenile or subacute form (PmS) and the chronic adult form (PmC). The human immunodeficiency virus (HIV) associated paracoccidioidomycosis (PmHIV) shares characteristics with both of the previously mentioned forms. The objective of this work was to describe the epidemiological, clinical and laboratory features of the PmHIV and to compare them with the ones of PmS and the PmC. A retrospective analysis of 119 patients with paracoccidioidomycosis was performed. Ninety four suffered the chronic form, 11 the subacute one and 14 were coinfected with HIV. Patients with PmHIV presented a CD4+ T lymphocytes median of 70.5 cells/μl, 71.4% had fever, 64.3% had a miliary pattern on the chest radiography, 64.3% had hepatosplenomegaly, 64.3% had mucosal lesions and 50% had skin lesions. One patient died during his hospitalization. The clinical presentation of Pm in patients with HIV resembled the subacute form with fever, hepatomegaly and skin lesions. However, they also tended to present mucosal lesions, positive serology for Pm and pulmonary parenchyma lesions as usually seen in PmC (9/14 PmHIV patients had overlapping features, while 4/14 PmHIV patients clinically resembled PmS and 1/14 PmC). The incidence of Pm has not changed with the burden of AIDS as it has happened with other fungal infections but it appears clinically different from the classic clinical forms of the disease.